2021
DOI: 10.3389/fonc.2021.614172
|View full text |Cite
|
Sign up to set email alerts
|

Using Deep Neural Network to Diagnose Thyroid Nodules on Ultrasound in Patients With Hashimoto’s Thyroiditis

Abstract: ObjectiveThe aim of this study is to develop a model using Deep Neural Network (DNN) to diagnose thyroid nodules in patients with Hashimoto’s Thyroiditis.MethodsIn this retrospective study, we included 2,932 patients with thyroid nodules who underwent thyroid ultrasonogram in our hospital from January 2017 to August 2019. 80% of them were included as training set and 20% as test set. Nodules suspected for malignancy underwent FNA or surgery for pathological results. Two DNN models were trained to diagnose thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Hou et al. used a deep learning-based CAD system to distinguish nodules in the context of HT, and the AUC was significantly higher than that of three groups of radiologists with different years of experience (all P < 0.05) ( 31 ). The above studies demonstrated the diagnostic feasibility of CAD systems based on deep learning for nodules in HT, but only static images of the largest section of the nodule were input into the CAD system.…”
Section: Discussionmentioning
confidence: 99%
“…Hou et al. used a deep learning-based CAD system to distinguish nodules in the context of HT, and the AUC was significantly higher than that of three groups of radiologists with different years of experience (all P < 0.05) ( 31 ). The above studies demonstrated the diagnostic feasibility of CAD systems based on deep learning for nodules in HT, but only static images of the largest section of the nodule were input into the CAD system.…”
Section: Discussionmentioning
confidence: 99%
“…As most of the nodules with benign features on grey‐scale ultrasound and follow‐up observation are not recommended for further CEUS and FNA, resulting in a high rate of malignancy in the included nodules. In addition, a previous study 21 suggested that the background of Hashimoto's thyroiditis may affect the diagnostic accuracy of AI, but this measure was not included in this study, and further studies will be conducted at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…However, HT is more difficult for radiologists to recognize compared with nodules. Additionally, HT is commonly combined with thyroid nodules, such as nodule goiter, adenoma, and cancer ( 31 ), whereas HT with thyroid nodules can induce significant interference in the US diagnosis of thyroid cancer ( 32 ). Thus, improving the accuracy of ultrasonic identification of HT can play a prominent role, which may not be limited to the early diagnosis of the disease only, and can also aid in the identification of thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%